Berantas Stunting Dan Penatalaksanaan Permasalahan Kesehatan Menuju Masyarakat Cerdas Bersama Mahasiswa Farmasi Stikes Harapan Ibu Jambi - Meirista, Indri; Yulyana, Zahara; Maharani, Silviya; Nurhidayanti, Rts. Reni; Aisyah, Andi; Febiyanti, Lidya; Ningrum, Wesi Alfiah; Wahyuni, Sisca Tri (Yayasan Cendekia Gagayunan Indonesia, 2025)
Abstract: Stunting is a global health problem that affects the physical growth and cognitive development of children. Studies show that the prevalence of stunting in Indonesia is still high, affecting people's quality of life and productivity. This article discusses strategies to combat stunting and the management of health problems towards a smart society. Preventive approaches are the main focus in overcoming stunting. Public health education on balanced nutrition and good sanitation practices are key to preventing stunting. Supplementary feeding programs for pregnant women and children under five and monitoring child growth are important strategies in stunting intervention. In addition, the management of other health problems is also needed to create a smart society holistically. Efforts to prevent and treat infectious diseases such as diarrhea, respiratory infections, and other infectious diseases must be improved. An integrated and affordable health care system is crucial in providing full access to quality health services. A smart society requires an environment that supports optimal growth and development. Therefore, cross-sector collaboration is important in addressing stunting and other health issues. The government, non-governmental organizations, the private sector and communities need to come together to implement sustainable policies and innovative programs to improve the overall health and well-being of the community. In conclusion, eradicating stunting and managing health problems are crucial steps towards a smart society. Cross-sector collaboration, preventive approaches, and affordable health services are needed to achieve this goal.